Lignin from the sugar palm's fiber (Arenga pinnata merr.) as a potential active compound in packaging; Case Studies in Chemical and Environmental Engineering; Vol. 11 - Syahidah; Lestari A.S.R.D.; Arif A.; Taskirawati I.; Makkarennu; Fardhatillah; Zhafira R.; Pratama M. R. A; Sulaeha S.; Anita S. H.; Ghozali M.; Sari F. P.; et al. (2025, 2025)
This study evaluated the chemical-thermal properties of lignin isolated from the alkaline black liquor of sugar palm (Arenga pinnata Merr.) stem fibers using low-concentration hydrochloric acid. The effect of lignin as a filler in sugar palm starch-lignin biofilms was also assessed. Successful extraction of alkaline lignin was confirmed through FTIR analysis, which identified characteristics of lignin monomer and functional groups such as syringyl (wavelength of 1325 and 1114 cm−1), guaiacyl (wavelength of 1214 cm−1), and aromatic compounds (wavelength at 699, 1454, 1515, and 1635 cm−1). The lignin obtained had 67.26 % purity, a 15.61 % yield, and an equivalent weight of 947.42. This isolated lignin was combined with sugar palm starch to create biofilms, and their mechanical, chemical, thermal, and morphological properties, as well as swelling, UV shielding, and antioxidant capacity, were evaluated. The addition of lignin improved the thermal and mechanical properties of the biofilms as shown by increasing the mass residue by 18.23 % for starch-sugar palm lignin bioplastic compared to 0.22 % for starch bioplastic. The lignin introduction into the starch matrix enhanced the UV-blocking capacity of biofilm and created rougher surfaces. The antioxidant of starch-lignin biofilm is slightly higher (7.53 %) than starch biofilm (5.69 %), however, this value is much lower than starch-commercial lignin bioplastic and butylated hydroxytoluene (BHT) comparison. The relatively low purity of sugar palm lignin might contributed to un-optimal value. The breaking strain of biofilm by lignin addition tends to increase than starch biofilm indicating its potential for food packaging which requires high creepability. It can be also confirmed that lignin increased the contact angle of starch biofilm. The study demonstrated the feasibility of extracting lignin from sugar palms and observed the potential use in starch-based biofilms for active packaging materials by improving antioxidant and UV barrier properties